Predictive Factors of Pulmonary Embolism in Older Patients with SARS-CoV-2: The OCTA-COVID-19 Study - Quezada Feijoó, Dolores Maribel; Ramos Sánchez, Mónica; Lozano Montoya, Isabel; Toro, Rocío; Jaramillo Hidalgo, Javier; Fernández de la Puente Rodríguez, Eva; Garmendia Prieto, Blanca; Carrillo García, Pamela; Cristofori, Giovanna; Goñi Rosón, Saleta; Ayala Muñoz, Rocío; Sarró, Mónica; et al. (My University, 2021)
Background: The risk of pulmonary embolism (PE) has not been studied in older patients affected by COVID-19. We aimed to assess PE incidence and risk factors in a population of older patients infected with SARS-CoV-2. Methods: An ambispective, observational cohort study. A total of 305 patients ¿ 75 years old had the SARS-CoV-2 infection from March to May 2020. The incidence rate of PE was estimated as the proportion of new cases within the whole sample. Youden¿s index was used to assess the cutoff point of D-dimer. To select factors associated with the risk of PE, timeto-event analyses were performed using cause-specific hazard models. Results: In total, 305 patients with a median age of 87 years (62.3% female) were studied; 67.9% were referred from nursing homes and 90.4% received any type of anticoagulation. A total of 64.9% showed frailty and 44% presented with dementia. The PE incidence was 5.6%. The cutoff value of a D-dimer level over 2.59 mg/L showed a sensitivity of 82.4% and specificity of 73.8% in discriminating a PE diagnosis. In the multivariate analysis, the factors associated with PE were previous oncological events and D-dimer levels. Conclusions: The PE incidence was 5.6%, and major risk factors for PE were oncological antecedents and increased plasma D-dimer levels.
Keywords: pulmonary embolism; older; COVID-19